2016
DOI: 10.1159/000446149
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Brush Cytology Revisited

Abstract: Purpose: To evaluate the diagnostic yield of biliary brush cytology and the factors affecting positive results in patients with biliary strictures. Patients and Methods: The medical records of all patients who underwent endoscopic retrograde cholangiopancreatography (ERCP) with biliary brush cytology at our institution from November 2004 to December 2013 were reviewed in this retrospective study. The yield of positive brush cytology and the factors affecting positive yield, such as stricture location, age, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Because of their deep anatomical position, obtaining tissues from proximal strictures is more technical, and the cell volume obtained from proximal strictures is theoretically less than that obtained from distal strictures with the instruments used during ERCP because the intrahepatic bile duct is less accessible. However, in studies, the conclusions were varied . Our study identified that the diagnostic accuracy between proximal and distal strictures was not significantly different for RC and the combination of two methods.…”
Section: Discussionmentioning
confidence: 64%
“…Because of their deep anatomical position, obtaining tissues from proximal strictures is more technical, and the cell volume obtained from proximal strictures is theoretically less than that obtained from distal strictures with the instruments used during ERCP because the intrahepatic bile duct is less accessible. However, in studies, the conclusions were varied . Our study identified that the diagnostic accuracy between proximal and distal strictures was not significantly different for RC and the combination of two methods.…”
Section: Discussionmentioning
confidence: 64%
“…Although biliary brush cytology is the most widely used tissue sampling technique, it has been associated with modest sensitivity in a large number of studies [3, 18, 21]. The current literature indicates a diagnostic sensitivity for cancer detection ranging from 6 to 65% [1, 10-22]. In a 10-year review of the literature, Burnett et al [21] identified 16 studies (involving a total of 1,556 patients).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, higher sensitivities were reported by Urbano et al [19], Arvanitakis et al [20], and Temiño López-Jurado et al [10] (65, 63, and 61%, respectively). Several factors have been highlighted to explain this large variability in sensitivity, such as the endoscopic technique, type of brush, use of dilatation and basket, cytological techniques, and cytological criteria for malignancy, interpathologist variation for biliary cytology interpretation, patient age, and the type, localization, and length of the tumor [1, 10, 13, 15, 18, 21, 22, 24]. In the current study, we found an overall sensitivity of 52.5%, a result in line with the previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations